Optimization of Electronic Traffic Law Enforcement (ETLE) by the Gakkum Satlantas Unit of Polresta Pati in Reducing Traffic Violations - Bima Cahya Juliansyah (Advances in Police Science Research Journal, 2024)
The focus of research in this final project is on optimizing ETLE enforcement by the Pati Police Satlantas law enforcement unit in reducing past violations. The focus of this research is considered important because traffic violations in Pati Regency have increased. Therefore, the Satlantas Polresta Pati Police Unit is trying to optimize the enforcement of ETLE so that its implementation is in accordance with the telegram from the National Police Chief Number ST/2264/X/HUM.3.4.5./2022 concerning the prohibition of taking manual action against traffic violators. This study aims to: (1) Describe the application of ETLE by the Satlantas Polresta Pati Police Unit; and (2) Describe the organizational resources of the enforcement of ETLE by the Satlantas Polresta Pati Unit in reducing traffic violations. The author uses a qualitative approach with a type of field research to obtain data directly by observation. Several theories and concepts used in this study, namely: management theory, communication theory, the concept of community education, the concept of Traffic Information, and the concept of traffic accidents. Data obtained from primary and secondary data sources. The author uses data triangulation to obtain data validity. The findings in this study are: (1) The implementation of ETLE by the Satlantas Satlantas Unit of the Pati Police has not been carried out properly in planning, organizing, implementing and supervising; and (2) ETLE Organizational Resources by the Satlantas Satlantas Unit of the Pati Police in reducing traffic violations have not been optimal in accordance with Law Number 22 of 2009 concerning Road Traffic and Transportation. The conclusions in this final project are: (1) Implementation of ETLE by the Satlantas Satlantas Unit of the Pati Police is not optimal; and (2) Organizational Resources of ETLE by the Satlantas Satlantas Unit of the Pati Police in reducing traffic violations are not yet optimal.